A STUDY ON MICRO ENTERPRISES IN MADURAI DISTRICT – WITH SPECIAL REFERENCE TO ENTREPRENEURSHIP DEVELOPMENT. - JAYALAKSHMI, K.; Rengaraj, S. (International Journal of Psychosocial Rehabilitation, 2020)
–This Study gives a brief analysis of the respondents’ role of DIC in Entrepreneurship Development. Entrepreneurship is the process of designing, launching and running a new business which is often initially a small business and selecting top managers for day to day operations of the enterprise. The main objectives of the study are to analysis the attitude of the respondents towards role of DIC in Entrepreneurship development. Data were collected from 175 respondents and a sample size of 25 each from of all the seven Taluks. The researcher used convenient sampling method to collect data from the sample respondents. Primary data were collected from the entrepreneurs of micro enterprises directly. Secondary data are collected from journal, magazine, newspaper and relevant books and website. Percentage analysis and chi-square test were used to analyze the data. The study in Madurai district from August 2019 to December2019.Finally Conclusions was drawn and suggestions were offered.